The Relationship of the 4P Model to Purchasing Decisions: Evidence on Residential Property - Naida, Andi Shopia; Anita, Rossy Dwi; Arsyad, Muh. Rezky Pangeran Syafar (JAMPE (Journal of Asset Management and Public Economy), 2024)
This paper explores the application of the 4P model (product, price, place, promotion) in analyzing the factors that influence house purchasing decisions in the Anging Mammiri Residence housing complex, Makassar City. Through quantitative research with a descriptive approach and collecting primary data through questionnaires, validity and reliability tests were carried out on these variables to ensure the robustness of the variables and the formation of a linear relationship between the variables. The population in this research is the number of consumers who have bought a house at Anging Mammiri Residence, Makassar City from 2016 to 2022. In this research, the sample was taken using the Census Sampling technique where the researcher took the entire sample or part of that number. Questionnaires were distributed to all home buyers totaling 131 respondents. However, at the data processing stage, 61 respondents did not return the questionnaire. So, the number of samples used was 70 respondents. The research results found that product, price, location and promotion had a significant and positive influence on the decision to purchase a house at Anging Mammiri Residence, Makassar City. This research contributes to understanding the elements of the marketing mix and analyzes the 4P model in shaping consumer decisions and its implications for the property market. Apart from that, it contributes to the government as a source of literature in formulating appropriate policies and in building infrastructure and regional development such as roads and other public facilities.